2019
DOI: 10.5194/acp-19-12779-2019
|View full text |Cite
|
Sign up to set email alerts
|

Integration of airborne and ground observations of nitryl chloride in the Seoul metropolitan area and the implications on regional oxidation capacity during KORUS-AQ 2016

Abstract: Abstract. Nitryl chloride (ClNO2) is a radical reservoir species that releases chlorine radicals upon photolysis. An integrated analysis of the impact of ClNO2 on regional photochemistry in the Seoul metropolitan area (SMA) during the Korea–United States Air Quality Study (KORUS-AQ) 2016 field campaign is presented. Comprehensive multiplatform observations were conducted aboard the NASA DC-8 and at two ground sites (Olympic Park, OP; Taehwa Research Forest, TRF), representing an urbanized area and a forested s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 106 publications
1
16
0
Order By: Relevance
“…Downwind plume chemistry is also further investigated and fingerprinted using the onboard DC-8 observations and an explicitly constrained 0-D photochemical box model simulation. Constituent profiles at TRF were also measured using ground-based instrumentation such as O3 lidar (Sullivan et al, 2016;, electrochemical cell (ECC) O3-sondes, and aerosol backscatter. Surface observations of O3, NO2, toluene, and isoprene at TRF are also presented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downwind plume chemistry is also further investigated and fingerprinted using the onboard DC-8 observations and an explicitly constrained 0-D photochemical box model simulation. Constituent profiles at TRF were also measured using ground-based instrumentation such as O3 lidar (Sullivan et al, 2016;, electrochemical cell (ECC) O3-sondes, and aerosol backscatter. Surface observations of O3, NO2, toluene, and isoprene at TRF are also presented.…”
Section: Methodsmentioning
confidence: 99%
“…Recent chemical simulations performed during the KORUS-AQ period by Miyazaki et al, 2018 also reveal that observed boundary 10 layer O3 can be as much as 30 ppbv different with dynamic and stagnant flow regimes. Supporting work at TRF has also shown that fast oxidation rates (Kim et al, 2018) and overall oxidation capacity (Jeong et al, 2018) at TRF can exacerbate severe pollution events.…”
Section: Introductionmentioning
confidence: 99%
“…A high-resolution PTR-ToF-MS (Ionicon Analytik GmbH) (de Gouw and Warneke, 2007;Jordan et al, 2009) was deployed at the TRF site. The instrument was operated with a drift tube temperature of 60 • C, 560 V drift voltage, and 2.27 mbar drift tube to maintain the field density ratio (E / N) of 126 Td.…”
Section: Ptr-tof-ms Measurementsmentioning
confidence: 99%
“…As the only information we have is the molecular composition, we identified multiple isomers with different functional groups and thus different reactivity. We have extensively reviewed previous publications (Williams et al, 2001;De Gouw et al, 2003;de Gouw and Warneke, 2007;Jordan et al, 2009;Ruuskanen et al, 2011;Müller et al, 2012;Koss et al, 2017) identifying ambient VOCs using PTR-MS with both quadrupole and time-offlight systems to identify possible compounds. For example, for the m/z of 75.043, there are four possible compounds including hydroxy acetone, propionic acid, methyl acetate, and ethyl formate.…”
Section: Oh Reactivity Calculationmentioning
confidence: 99%
See 1 more Smart Citation